Konstruksi Dakwah Multikultural Menurut Roza Melina Mazlin - Pamungkas, Yudha Catur; Zuhriyah, Luluk Fikri; Purnomo, Ryan (Kamaya: Jurnal Ilmu Agama, 2025)
Indonesia is a country with a high degree of cultural, religious, and ethnic diversity, which presents complex challenges in the implementation of Islamic da'wah. The conventional da'wah approach that tends to be homogeneous is considered incapable of answering the needs of a pluralist society. Therefore, multicultural da'wah emerged as an alternative that emphasized the importance of respecting diversity and inclusivity. This research aims to examine the concept of multicultural da'wah, its implementation in Indonesia, and its impact on the creation of social harmony. The research uses a qualitative method with an analytical descriptive approach. Data were collected through literature studies, in-depth interviews with religious leaders, and field observations on communities that implement multicultural da'wah. The results of the study show that multicultural da'wah emphasizes interreligious dialogue, tolerance-based character education, and the use of social media as the main means of conveying the message of da'wah. Intensive interfaith dialogue helps create space for mutual respect, reduce prejudice, and strengthen solidarity in a diverse society. Multicultural education also plays an important role in instilling the values of tolerance from an early age. Meanwhile, social media has proven to be an effective platform to reach the younger generation, expand the reach of da'wah, and increase public awareness of the importance of maintaining social harmony. This study also found several challenges that hinder the effectiveness of multicultural da'wah, including resistance from conservative groups who still adhere to traditional approaches and low understanding of multicultural literacy among preachers. The conclusion of this study is that multicultural da'wah is relevant as a strategic approach in creating an inclusive, fair, and harmonious society in Indonesia. By integrating multicultural education, interfaith dialogue, and modern technology, multicultural da'wah can strengthen peace and prevent conflicts stemming from identity differences.